DAMPAK PENERAPAN MODEL COOPERATIVE LEARNING TIPE PICTURE AND PICTURE BERBANTUAN MEDIA FLASH CARD TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI MURID SEKOLAH DASAR - Jajat Sudrajat; Asep Nurhuda; Rukman Aca (STKIP Subang, 2026)
This study was motivated by the low descriptive text writing ability of elementary school students, particularly in expressing ideas into coherent and concrete sentences. The Cooperative Learning Picture and Picture model assisted by Flash Card media was applied to address this problem because it provides visual stimuli that help students develop ideas logically. This study aimed to (1) explain the impact of applying this model on the descriptive text writing ability of fourth-grade elementary school students, and (2) determine the extent of the improvement. This study used a quantitative approach with a quasi-experimental type and a Non-Equivalent Control Group Design. The sample consisted of 28 students from class IV C as the experimental group and 28 students from class IV A as the control group at SDN Cikampek Selatan 1. Data were collected through pretest and posttest, then analyzed using descriptive statistics, the N-Gain test, prerequisite tests, hypothesis testing, and simple linear regression with IBM SPSS 25. The results showed that the experimental group's average posttest score was 97.57, higher than the control group's 94.43, although the initial abilities of both groups were relatively equal. The experimental group's average N-Gain was 0.86 (high category), while the control group's was 0.68 (moderate category). The Independent Sample t-Test showed a t-value of 4.446 with a significance of 0.000 (< 0.05), so H0 was rejected. Simple linear regression showed an R Square of 0.268, meaning the model contributed 26.8% to the improvement in students' writing ability. It can be concluded that the Cooperative Learning Picture and Picture model assisted by Flash Card media has a positive and significant impact on elementary school students' descriptive text writing ability.